State of the Union Addresses - Arthur, Chester Alan, 1829-1886 (Salt Lake City, UT : Project Gutenberg, 2004)
"State of the Union Addresses" by Chester Alan Arthur is a collection of presidential addresses reflecting on the state of the nation and its foreign relations, written during the late 19th century. It encompasses the official messages presented by Arthur to the United States Congress, providing insight into the political climate, economic conditions, and notable national events of his presidency. At the start of this compilation, Arthur speaks solemnly about the calamities and achievements faced by the nation since the previous Congress convened. He expresses gratitude for the country's prosperity, alluding to its plentiful harvests and stable health, while also mourning the loss of his predecessor, President James Garfield. The addresses delve into various topics, including international diplomatic relations, with updates on treaties, negotiations regarding the construction of the Panama Canal, and issues regarding trade with foreign nations. Each address reflects the president's assessments and recommendations to Congress, setting a formal yet personal tone as he engages with domestic and international matters of state. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by James Linden. HTML version by Al Haines.
Keywords: Presidents -- United States -- Messages; United States -- Politics and government -- Sources